Digital government and carbon emissions: evidence from China - Yi, Junling (Frontiers in Environmental Science, 2025)
With the continuous modernization of national governance, the role of digital government construction in environmental protection and sustainable development has become increasingly prominent. This study explores the intrinsic link between digital government construction and carbon emissions and the mechanism of its influence based on 30 provincial-level panel data in China from 2017 to 2021. The study finds that digital government construction can significantly suppress carbon emissions, and this conclusion still holds after considering endogeneity issues and after multiple robustness tests. The study further reveals that digital government can inhibit carbon emissions through the internal mechanism of promoting industrial structure upgrading and green technology innovation. In addition, the inhibiting effect of digital government on carbon emissions is more pronounced in eastern and central provinces, provinces with higher levels of government transparency, higher levels of digital government development, and higher intensity of environmental regulation. This study provides an important reference for understanding the role of digital government construction in promoting green development and achieving carbon emission reduction targets.